The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1016/j.neuroimage.2017.04.018
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of accurate automatic hippocampal segmentation methods

Abstract: The hippocampus is one of the first brain structures affected by Alzheimer's disease (AD). While many automatic methods for hippocampal segmentation exist, few studies have compared them on the same data. In this study, we compare four fully automated hippocampal segmentation methods in terms of their conformity with manual segmentation and their ability to be used as an AD biomarker in clinical settings. We also apply error correction to the four automatic segmentation methods, and complete a comprehensive va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 37 publications
(31 citation statements)
references
References 50 publications
2
28
1
Order By: Relevance
“…Twenty subjects were selected from each of the following clinical subgroups: normal controls, mild cognitive impairment, and Alzheimer's disease. Since this dataset was previously used to compare several state‐of‐the‐art algorithms (Zandifar et al, ), for our experiments, we use the same data (e.g., previously preprocessed as described in Zandifar et al) to enable meaningful comparisons with the results reported in the aforementioned work. Pre‐processing consisted of patch‐based (PB) denoising (Coupé et al, ), N3 nonuniformity correction (Sled, Zijdenbos, & Evans, ), linear intensity normalization to the range [0,100], and affine registration to the MNI‐ICBM152 template (Fonov et al, ) with 1 × 1 × 1 mm 3 resolution.…”
Section: Experiments and Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Twenty subjects were selected from each of the following clinical subgroups: normal controls, mild cognitive impairment, and Alzheimer's disease. Since this dataset was previously used to compare several state‐of‐the‐art algorithms (Zandifar et al, ), for our experiments, we use the same data (e.g., previously preprocessed as described in Zandifar et al) to enable meaningful comparisons with the results reported in the aforementioned work. Pre‐processing consisted of patch‐based (PB) denoising (Coupé et al, ), N3 nonuniformity correction (Sled, Zijdenbos, & Evans, ), linear intensity normalization to the range [0,100], and affine registration to the MNI‐ICBM152 template (Fonov et al, ) with 1 × 1 × 1 mm 3 resolution.…”
Section: Experiments and Resultsmentioning
confidence: 99%
“…We further compared several variants of our CNN‐based method with several other popular and/or state‐of‐the‐art segmentation methods on the same dataset using the segmentations previously produced in the work of Zandifar et al (), which includes results for four different methods, both before and after applying EC (Wang et al, ), a machine learning based wrapper which attempts to correct systematic errors made by the initial host segmentation method. The methods included are FreeSurfer (Fischl, ), ANIMAL (Collins & Pruessner, ) (a multiatlas technique combining nonlinear registration with majority‐vote label fusion), traditional PB segmentation (Coupé et al, ) (a multiatlas technique combining linear registration with PB label fusion), and an augmented approach combining PB segmentation with nonlinear registration.…”
Section: Experiments and Resultsmentioning
confidence: 99%
See 3 more Smart Citations